The evolutionary pathway to obligate scavenging in Gyps vultures - JACKSON, ANDREW; TANNER, COLBY (PLoS, 2011)
The evolutionary pathway to obligate scavenging in Gyps vultures remains unclear. We propose that communal roosting plays a central role in setting up the information transfer network critical for obligate scavengers in ephemeral environments and that the formation of a flotilla-like foraging group is a likely strategy for foraging Gyps vultures. Using a spatial, individual-based, optimisation model we find that the communal roost is critical for establishing the information network that enables information transfer owing to the spatial-concentration of foragers close to the roost. There is also strong selection pressure for grouping behaviour owing to the importance of maintaining network integrity and hence information transfer during foraging. We present a simple mechanism for grouping, common in many animal species, which has the added implication that it negates the requirement for roost-centric information transfer. The formation of a flotilla-like foraging group also improves foraging efficiency through the reduction of overlapping search paths. Finally, we highlight the importance of consideration of information transfer mechanisms in order to maximise the success of vulture reintroduction programmes.
PUBLISHED
Keywords: ecology; animal behaviour; foraging; computer model; simulation; evolution